Associations between Community‐Acquired Pneumonia and Proton Pump Inhibitors in the Laryngeal/Voice‐Disordered Population. (13th November 2018) - Cohen, Seth M.; Lee, Hui‐Jie; Leiman, David A.; Roy, Nelson; Misono, Stephanie
Abstract : Objectives: To examine the relationship between community‐acquired pneumonia (CAP) and proton pump inhibitor (PPI) treatment among patients with laryngeal/voice disorders. Study Design: Retrospective cohort analysis. Setting: Large national administrative US claims database. Subjects and Methods: Patients were included if they were ≥18 years old; had outpatient treatment for a laryngeal/voice disorder from January 1, 2010, to December 31, 2014 (per International Classification of Diseases, Ninth Revision, Clinical Modification codes); had 12 months of continuous enrollment prior to the index date (ie, first diagnosis of laryngeal/voice disorder); had no preindex diagnosis of CAP; and had prescription claims captured from 1 year preindex to end of follow‐up. Patient demographics, comorbid conditions, index laryngeal diagnosis, number of unique preindex patient encounters, and CAP diagnoses during the postindex 3 years were collected. Two models—a time‐dependent Cox regression model and a propensity score–based approach with a marginal structural model—were separately performed for patients with and without pre–index date PPI prescriptions. Results: A total of 392, 355 unique patients met inclusion criteria; 188, 128 (47.9%) had a PPI prescription. The 3‐year absolute risk for CAP was 4.0% and 5.3% among patients without and with preindex PPI use, respectively. For patients without and with pre–index date PPI use, the CAP occurrence for a person who had already received a PPI is 30% to 50% higher, respectively, than for a person who had not yet had a PPI but may receive one later. Conclusions: Patients without and with pre–index date PPI use experienced a roughly 30% to 50% increased likelihood of CAP, respectively, as compared with patients who had not had PPI prescriptions.